SPEAKING ANXIETY: EXPERIENCES OF PRE-SERVICE TEACHERS’ IN EFL CONTEXT LEARNING AT THE SECOND, FOURTH AND SIXTH SEMESTER WITHIN GENDER BASED IN ENGLISH DEPARTMENT OF MULAWARMAN UNIVERSITY - Maharyadin, Andi; Sunggingwati, Dyah; Rusmawaty, Desy (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
Anxiety in speaking particularly in a foreign language context is considered as an issue that requires more investigation since it is one feature that hinders students’ performance and achievement. This study aims to examine the level of pre-service English teachers’ speaking anxiety at the second, fourth and sixth semesters. Using a survey study, the respondents were 274 of pre-service English teachers, 190 females and 84 males. The questionnaire was employed to gather the data. The finding of this study revealed that pre-service English at all semesters had moderate level of speaking anxiety. Moreover, within gender-based context, male students tended to have lower language anxiety than the female students.